(3OjhGf CHj HcQ Hf SGde GdYdhi GdMVQeis - (3CHh HcQ Hf SGde Hf YHO Gddg GdSbGa GdMVQeqj,J (B992 (3g` s
(3ChdgG (B:s
(3GdTjN GdcHjQ GdaNQ CHh HcQ Hf GdSjO GdYGQa HGddg SGde Hf YHO Gddg hbGd SbJfi HcGS GdehO cGS GdehOI s
(3BNQgG (B:s
(3Ke GdUdGI Ydi GdfHj hBdg eG MQcJ QjM GdUHG CZUGfG JeJ hHGdNjQ YeJ s
(3Vef eLehY , JQJjHgG (B: 1s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B62s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs